Application of gastrointestinal decompression method in determining tip position of the triple-lumen nasointestinal tube in critically ill patients (胃肠减压法在危重症患者三腔鼻肠管位置判断中的应用) - WANG Zhimin (王志民); LI Xuejing (李雪晶); QIAO Shouang (乔首昂) (中西医结合护理)
Objective The aim of this study is to explore the accuracy of using gastrointestinal decompression method to determine the tip position of the triple-lumen nasointestinal tube in critically ill patients. Methods A retrospective analysis was conducted on the medical records of 120 critically ill patients with indwelling triple-lumen nasointestinal tubes from June 2020 to April 2022. All patients underwent blind insertion of a triple-lumen nasointestinal tube. The patients were divided into an experimental group and a control group, where the experimental group used a gastrointestinal decompression device to connect the suction cavity with the opening in the stomach, and combined with auscultation and liquid reflux to measure pH value to determine whether the tip of the catheter passed through the pylorus; The control group only used auscultation and pH measurement with liquid reflux to determine whether the catheter position passed through the pylorus. Bedside X-ray was used to confirm the accurate position of the catheter tip. Results Among the 65 cases in the experimental group, 59 cases were successfully catheterized and 6 cases failed by the initial judgment, consistent with the results of bedside X-ray. Among the 55 cases in the control group, 46 cases were catheterized and 9 cases failed by the initial judgment, but only 39 cases were successful and 16 cases failed by the judgment of X-ray. There was a significant difference in the accuracy of catheterization between the two groups (χ2=8. 785, P=0. 003). Conclusion Gastrointestinal decompression method can quickly and accurately determine the tip position of the nasointestinal tube, which is of great help for clinical work. (目的 探讨运用胃肠减压法判断危重症患者三腔鼻肠管位置的准确性。方法 回顾性分析2020年6月—2022年4月120例留置三腔鼻肠管的危重症患者的病历资料。所有患者均为盲插法留置的三腔鼻肠管。根据鼻肠管导管尖端位置判断方法不同将患者分为研究组和对照组, 其中研究组采用胃肠减压装置连接开口在胃内的吸引腔, 并结合听诊和回抽液体测pH值的方法判断导管尖端是否通过幽门; 对照组仅使用听诊和回抽液体测pH值的方法判定导管位置是否通过幽门。床旁X线被用来证实导管尖端的准确位置。结果 研究组65例患者中, 初步判断59例置管成功, 6例失败, 与床旁X线的结果一致; 对照组55例患者中, 初步判断46例置管成功, 9例失败, 实际成功39例, 失败16例。两组置管准确率差异有统计学意义(χ2=8. 785, P=0. 003)。结论 胃肠减压法能够快速、准确地判断鼻肠管位置, 对临床工作具有重要帮助。)